2011
DOI: 10.1016/s0034-7094(11)70039-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Work-Related Variables on Quality of Life of Anesthesiologists in the City of João Pessoa

Abstract: It was observed that work-related variables had a significant correlation with QOL. In addition to expressive statistical difference between the domains of QOL scale and the number of working hours, the same divergence was also observed regarding the environmental domain and monthly income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Santos et al [ 10 ] conducted a study in which the labor-related impact on QOL was identified using the WHOQOL-BREF and reported that work-related variables (total on-call hours, labor hours, sleep pattern, and physical activities) were significantly correlated with QOL. This study also found that the environmental domain may influence monthly income.…”
Section: Resultsmentioning
confidence: 99%
“…Santos et al [ 10 ] conducted a study in which the labor-related impact on QOL was identified using the WHOQOL-BREF and reported that work-related variables (total on-call hours, labor hours, sleep pattern, and physical activities) were significantly correlated with QOL. This study also found that the environmental domain may influence monthly income.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the physical and psychological domains of plastic surgeons were inferior to those of several health professionals, 11 such as nurses and nursing technicians, 12 anesthetist, and nonanesthetist physicians. 13 , 14 This may be related to the model of the profession that demands good physical health to perform surgeries and the need for psychological development in the treatment of patients and their complaints.…”
Section: Discussionmentioning
confidence: 99%